ANALISIS PENGARUH PERGERAKAN KENDARAAN MEMUTAR ARAH TERHADAP TUNDAAN DAN ANTRIAN DI JALAN PROFESOR SOEDARTO, SH. SEMARANG - Ferry Agriyoso; Aghus Majid S.; Bambang Riyanto; Ismiyati Ismiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The Problems Of Transportation that problem occur all this time was traffic jams. One of the traffic jams have been occur at Profesor Soedarto, SH Street which was caused by the movement of the vehicle turning direcyion and volume and traffic in the street. The movement of the vehicle turning direction was causing delays and queues on the roads. At this study, the analisis was done by using the referance based on the rules of indonesian Highway Capacity Manual and descriptive statistic analysis. The purpose of this study was to identify the level of service roads, identify the characteristics of delay and queue that occur due to variations in the duration of the vehicle turning direction at the and of the median, as well as provide an alternative solution. The method used to improve services an the area of roads is traffic management. The result of this study showed that the level of the service road can’t accomodate the number of vehicles passing on the roads. It can be seen from the degree of saturation (DS) which was more than one. Average delay stopped in the road to reach 10.19 seconds and result in long queues of 22 meters.. Best alternative solution of this study is the road widening.